FAKTOR YANG MEMPENGARUHI HARGA SAHAM SUB SEKTOR JASA KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Ryan Maulana; Mona Adriana (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
In general, the construction and building sector is one of the sectors that supports economic growth in Indonesia. Studies show that the construction sector is in the third position as the main source of Indonesia's economic growth. The growing construction sector made the Indonesian economy in 2017 grow by 5.01% and GDP by 10.38%. In the 2015-2019 period, the government is also aggressively implementing infrastructure development projects in Indonesia. From the existing data, the authors want to see how much influence government policies through macroeconomic variables affect the stock price of the construction sector and is supported by profitability ratios to see the company's performance in the capital market. This study uses the panel data method using the research object of 11 construction companies listed on the Indonesia Stock Exchange in 2015-2019. Through profitability ratio variables and macroeconomic variables. The results showed that simultaneously the variables EPS, ROA, ROE, inflation, interest rates, economic growth and exchange rates had an effect on stock prices. While partially EPS, ROE, economic growth, inflation, interest rates and exchange rates have an effect on stock prices.